2014
DOI: 10.1089/neu.2014.3439
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cerebral Edema after Traumatic Brain Injury Using an Osmotic Transport Device

Abstract: Traumatic brain injury (TBI) is significant, from a public health standpoint, because it is a major cause of the morbidity and mortality of young people. Cerebral edema after a TBI, if untreated, can lead to devastating damage of the remaining tissue. The current therapies of severe TBI (sTBI), as outlined by the Brain Trauma Foundation, are often ineffective, thus a new method for the treatment of sTBI is necessary. Herein, the reduction of cerebral edema, after TBI, using an osmotic transport device (OTD) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Cerebral edema is a common secondary disease following traumatic brain injury (TBI) which can be an important risk factor for mortality and poor outcome [1,2]. Therefore, the real-time continuous monitoring of cerebral edema plays important roles in disease observation, treatment guidance, surgery timing determination and prognosis evaluation for patients after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral edema is a common secondary disease following traumatic brain injury (TBI) which can be an important risk factor for mortality and poor outcome [1,2]. Therefore, the real-time continuous monitoring of cerebral edema plays important roles in disease observation, treatment guidance, surgery timing determination and prognosis evaluation for patients after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…It is intriguing to explore the use of hydrogels that can absorb excess liquid locally and potentially restore fluid homeostasis after CNS injury. A recent report by McBride et al [2014] utilizes an osmotic transport device (OTD) containing hollow fibers -filled with an osmotic agent that will create a chemical potential pressure for water -that are embedded within a highly swelling hydrogel material that can locally draw out excess water from the underlying brain tissue. The authors showed that application of the OTD after TBI reduced brain edema better than craniotomy alone.…”
Section: Design Considerations For Hydrogels Promoting Sci Repairmentioning
confidence: 99%
“…However, at least in the case of shape-memory materials, reversion to a larger size after injection may cause tissue damage similar to pressures exerted during in situ swelling. Alternatively, maximal swelling may be advantageous for hydrogels applied to the subdural space, where they could act to siphon off the excess fluid in the parenchyma that accumulates after SCI to prevent secondary damage, as recently demonstrated in TBI [McBride et al, 2014]. In either case, better strategies to improve control over hydrogel swelling by decoupling this property from other network properties are needed [Browning et al, 2011;Bearat et al, 2012;Shih and Lin, 2012].…”
Section: Fabrication Strategies For Injectable Hydrogelsmentioning
confidence: 99%
“…Synaptic plasticity, axonal sprouting, and cortical reorganization occur in the reversal process of diaschisis, which takes place after the early phases of TBI recovery (2). Proper rehabilitation strategies and pharmacologic interventions can manipulate late recovery (2,(16)(17)(18). The TBI is associated with direct and indirect costs.…”
Section: Introductionmentioning
confidence: 99%
“…The TBI is associated with direct and indirect costs. Direct costs involve the financial requirements for medical care, whereas indirect costs refer to those associated with the loss of productivity in individuals suffered from TBI, the family members that take care of them, and the costs of reduced participation in complex leisure or recreational activities (16,19). It has been reported that TBI patients suffer from at least one issue in the next year after their hospitalization (20).…”
Section: Introductionmentioning
confidence: 99%